Análise qualitativa da iluminação artificial e natural: estudo de caso das bibliotecas da UTFPR - Hara, Carlos Kazuhiko (2015)
The energy efficiency of buildings is an important issue to be discussed given the world energy scene. In Brazil, the rational use of energy is becoming increasingly evident in construction, especially in public buildings. A little less than three decades, PROCEL - National Program for Energy Conservation is looking for ways to combat the waste of energy in lighting area. The actions are to ratify the efficiency of light bulbs and building lighting systems. Lighting systems in buildings besides the artificial lighting, must have architectural features that allow use of natural light indoors. The study was conducted in fourteen libraries from UTFPR - Federal Technological University of Paraná. The environments studied were the collection and reading areas. In these environments, illuminance readings were held, provided by artificial lighting. Electronic models of buildings were created to simulate the entry of solar radiation inside the libraries. Data from the artificial lighting were evaluated by rqt-C - Technical Requirements for Energy Efficiency Level Quality for Commercial Buildings, and Public Services, and also by the Brazilian standard of interior lighting ISO / CIE 8995-1. The data of solar radiation were evaluated for the discomfort caused by glare inabilitator that users would be exposed. The results showed that the lighting systems have small deviations to be corrected and retrofit solutions have been proposed. The analyzes showed that the lighting systems of the studied libraries, the reconciliation between the average minimum luminance, energy efficiency and lighting comfort are relevant criteria forecast to be analyzed carefully during the library project, otherwise one of the factors mentioned will not be met.